Makna Tuhan Menyesal dalam Kitab Kejadian - Wassar, Sarah (REDOMINATE Jurnal Teologi dan Pendidikan Kristiani, 2020)
God has the highest authority over everything in the region including the living creatures in it. God saw that the evil of mankind is great on earth and that all the tendencies of his heart always produce only evil. God's hatred of human wickedness, He saw as the wounded and humiliated by man. He saw it as a gentle Father who saw the ignorance and hardness of His rebellious and disobedient heart, which not only made Him angry but also grieved. It is this sin and evil that makes God regret, that He has made man on earth, and that heartbreak (Genesis 6: 6-7). Thus God regrets causing God to be sovereign in expressing his authority over humans.